Students’ conceptual difficulties in learning curved-surface solids: The needs for RME-based interactive e-module - Yoga Tegar Santosa; Mutiara Hisda Mahmudah; Eko Ari Wibowo (Universitas Islam Negeri (UIN) Mataram, 2026)
[English]: This study aims to identify students’ difficulties in learning curved-surface solids, analyze the key aspects of their conceptual understanding, and explore their needs regarding content and digital features for an RME-based e-module. A mixed-method approach with a sequential explanatory design was employed. The participants consisted of 94 ninth-grade students from a private junior high school in Surakarta, Indonesia. Data were collected using a questionnaire as well as in-depth interviews. Quantitative data were analyzed descriptively, while qualitative data were processed through reduction, display, and conclusion drawing. The findings reveal that students continue to struggle with visualizing three-dimensional shapes, understanding the structure and use of formulas for volume and surface area, and identifying components of curved-surface solids. Their conceptual understanding falls within the “moderate” category, with noticeable uncertainty in explaining, connecting, and applying concepts. Moreover, students require content that offers deeper conceptual explanations, step-by-step procedural examples, and contextualized exercises, highlighting the need for integrating the RME approach into the e-module. They also expect digital features such as 3D visualizations, tutorial videos, interactive object manipulation, and automated assessments. [Bahasa]: Penelitian ini bertujuan untuk mengidentifikasi kesulitan belajar dan menganalisis pemahaman konsep siswa pada materi bangun ruang sisi lengkung, serta mengeksplorasi kebutuhan mereka terhadap konten dan fitur e-module sebagai landasan pengembangan e-module berbasis realistic mathematics education (RME). Penelitian ini menggunakan pendekatan mixed-method dengan desain sequential explanatory. Partisipan terdiri atas 94 siswa kelas IX dari salah satu SMP swasta di Kota Surakarta, Indonesia. Data diperoleh melalui angket dan wawancara mendalam. Analisis data kuantitatif dilakukan secara deskriptif, sedangkan data kualitatif dianalisis melalui proses reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa siswa masih mengalami kesulitan dalam memvisualisasikan bentuk tiga dimensi, memahami struktur dan penerapan rumus volume serta luas permukaan, serta mengidentifikasi komponen bangun ruang sisi lengkung. Pemahaman konsep siswa berada pada kategori cukup dengan kecenderungan ketidakpastian dalam menjelaskan, menghubungkan, dan menerapkan konsep. Selain itu, siswa membutuhkan konten berupa penjelasan konseptual yang mendalam, contoh prosedural bertahap, dan latihan kontekstual yang menunjukkan perlunya integrasi pendekatan RME pada e-module. Siswa juga mengharapkan fitur digital seperti visualisasi 3D, video tutorial, manipulasi objek interaktif, dan asesmen otomatis.